Quantitative analysis of shoulder function and strength after breast reconstruction: A retrospective cohort study. Issue 24 (June 2018) - Myung, Yujin; Choi, Bomi; Kwon, Heeyeon; Heo, Chan Yeong; Kim, Eun-Kyu; Kang, Eunyoung; Jeong, Jae Hoon; Yang, Eun Joo
Abstract : Abstract: Immediate breast reconstruction (IBR) after mastectomy has been proven to affect patient quality of life, psychological well-being, and functional capacities. In the present study, we aimed to investigate the effect of breast reconstruction on postoperative shoulder function and muscle performance by evaluating isokinetic muscle performance tests. A retrospective chart review to collect data on shoulder function analysis with isokinetic muscle performance testing was performed among patients who received mastectomy with IBR from July 2013 to March 2015. Patients were categorized into 4 groups: a control group that underwent mastectomy without reconstruction, a tissue expander/implant insertion group, a pedicled latissimus dorsi (LD) flap group, and a free transverse rectus abdominis muscle (TRAM) flap group. Analysis of the groups at 1 to 3, 4 to 6, 7 to 9, 10 to 12, and 13 to 15 months postoperatively showed significant shoulder function improvement in the tissue expander/implant and TRAM groups as measured by linear regression analysis. Compared with the control group, patients who received immediate reconstruction with tissue expander/implant insertion or a TRAM flap showed statistically significant improvement in shoulder function after mastectomy. IBR with a TRAM flap or tissue expander/implant insertion were more beneficial for shoulder rehabilitation and for regaining function compared to mastectomy alone and breast reconstruction with a LD flap.